Comparison between metformin and glibenclamide as antidiabetic oral in gestational diabetes mellitus: a review - Ridhayani, Firda; I Dewa Agung Ayu Diva Candraningrat; Ilmi Nurhafizah; Karina Nurlitasari; Mardiana Siregar (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2023)
Gestational diabetes mellitus (GDM) is one of the most frequent clinical complications during pregnancy that affects up to 6% of women with pregnancies around the world. Gestational diabetes mellitus treatment used insulin as first-line therapy. In addition, several professional associations are also considering treatment using antidiabetic oral which has equivalent efficacy compared with insulin. However, many oral antidiabetic recommendations have been administered to treat GDM, including metformin and glyburide or glibenclamide. This article’s review aims to compare the usage between metformin and glyburide or glibenclamide in GDM patients. This review compared research results from PubMed as literature resources and the PRISMA flow chart as the protocol for the article selection process. Based on inclusion and exclusion criteria there are six research articles that are appropriate to the article’s topic and aim. Metformin is superior compared with glyburide or glibenclamide administration as antidiabetic oral in GDM. Metformin showed a significant effect in lowering preprandial and postprandial glucose level, elevating insulin sensitivity, while glibenclamide administration decreased dynamic pancreatic β-cell responsivity significantly and had a higher risk compared with insulin and metformin.